Filosofía de la ciencia y arqueología: el caso de la arqueología prehistórica anglosajona - Moro Abadía, Oscar (Complutum, 2007)
In this article, we examine the anglo-saxon archaeological interpretation of the philosophy of science throughout the last century. With reference to an idea developed by Jane Kelley and Marsha Hanen, we define the former interpretation as the “narrow perspective” of the philosophy of science. This approach has focused exclusively on the analytical tradition of the philosophy of science; the foremost example is the New Archaeology interest in logical positivism. In the second section, we examine the consequences of this narrow perspective and we conclude that it is necessary to develop a “wide perspective” of the philosophy of science in archaeology.